Studi Keberadaan Mineralisasi Uranium Di Daerah Biak Numfor, Provinsi Papua Barat - Suharji, Suharji; Subiantoro, Lilik; Syaeful, Heri; Widana, Kurnia Setiawan; Prabowo, Hery (BRIN Publishing, 2014)
This study was conducted based on the findings of radioactive minerals in the form of indication of relatively high radiation dose rate anomalies. The hypothesis underlying the existence of a high radiation dose rate is the deposition of uranium derived from basalt rock Auwea Formation, uranium enrichment derived from limestone to the soil surface, and the deposition of uranium resulted from the use of fertilizers in agriculture. Therefore the research aimed to obtain the conclusion of its hypotheses. Research methodology applied is geological mapping, radiometric measurement of uranium (U), thorium (Th), and potassium(K) in the field using RS 125 to determine in-situ grade of elements, radiometric measurements of plant fertilizer, sampling, and laboratory analysis of the element grade. Based on the analysis and evaluation of survey data it is known that in the area around Maryendi, Darmapis and Denafi, indicate the presence of anomalous zones which is characterized by the presence of uranium (U) dark brown soil – reddish brown, with the value of the radiation dose of 1.9 to 4,032.3 nSv/h and grade of uranium (U)has 20.27 to 325 ppm eU. Based on the analysis of source rock of uranium, it is concluded that limestone is the source rock of uranium in research area. The results of field observations of the fertilizer and basalt rock of Auwea Formation, it is found that no anomalies may indicate material/rock that acts as the source of uranium.